Body Fat Content of Bobwhites in Relation to Food Plantings in Kansas - Robert J. Robel (National Quail Symposium Proceedings, 2017)
A wildlife habitat improvement program was initiated on the Fort Riley Military Reservation in 1961 to increase winter food supplies for bobwhite quail (Colinus virginianus). As part of an ongoing evaluation of this program, 164 bobwhite quail were collected during the fall and winter of 1968-72 for fat analysis. Fat content in carcasses of birds collected <600 m from a food plot was compared with fat content of birds collected >900 m from a food plot. During winter months, birds collected near a food plot were significantly (P<0.10 to P<0.05) heavier than birds not having access to a food plot. Fat content of birds close to a food plot was likewise greater (P<0.10 to P<0.01) than fat content in birds not using food plots. Calculations indicate that birds close to food plots have sufficient energy reserves to provide a 79% greater protection against brief periods of food deprivation than birds far from a food plot. Fat energy reserves alone in a quail close to a food plot could provide sufficient energy for 2.0 days of survival whereas quail far from food plots contained fat energy reserves sufficient for only 1.1 days of survival. Reserve energy for animals is stored in the body mainly in the form of fatty acids. The quantity of stored reserve energy (fat) may be critical to the animal's survival during periods of food scarcity or extremely cold weather. Much work has been done on fat content, composition, and regulation in songbirds (8, 9, 10, 11, 12, 15, 16, 23, 24). Only recently has any attention been given to body fat reserves of wild gallinaceous birds under natural conditions. West and Meng (25) reported on the relationship of total fat and fatty acid composition to diet of willow ptarmigan (Lagopus lagopus) in Alaska while Moss and Lough (14) presented similar data for 3 species of grouse in Scotland. Almost no attention has been given to fat reserves of bobwhite quail even though it is known that fat reserves may be essential for bird survival during periods of dietary stress (15, 23 and others). The most recent book on bobwhite quail (22) does not even discuss the importance of maintaining adequate fat reserves in quail for winter survival and spring breeding. In fact, not until only very recently has any attention been focused on basic energetics of bobwhite quail (3). Earlier I included a small amount of body-fat data in an evaluation of food plantings for bobwhite quail in Kansas (18). The purpose of the study described herein was to gather more extensive data on body fat content in bobwhite quail, especially as related to seasonal changes and food plantings in Kansas.